Managing the environment: issues and priority actions for sustainable waste management in Uganda - Edodi, Sampson (African Geographical Review, 2023)
Several priority actions are required to ensure a healthy environment for all. One of the priority actions is to collect and manage wastes effectively and efficiently. In this theoretical study, we give a global waste management outlook, examined Africa’s waste management outlook and the impact of improper waste management, and focus on the issues and priority actions for sustainable waste management in Uganda. Further, the paper put forward that first, we should design the public sector waste reduction framework, which currently exists in most societies including the United Nations Environment. Second, design the private sector waste reduction framework, which is currently lacking in most societies. And third, develop an overlapping mechanism that would generate a stronger and more productive collaboration between the public sector and the private sector. Finally, the study advances a sustainable inclusive waste management framework to operationalize the priority actions in managing wastes in informal settlements.
Keywords: Environmental management; Waste generation; Solid waste; Waste management policy; Waste control